Access to housing in Cape Town : do young people move smoothly from parental housing to independent living arrangements? - Chisonga, Nixon (Department of Social Development, 2014)
Most international and local (South African) research on housing examine housing tenure in terms of static categories, - i.e. does someone own or rent their accommodation - without capturing either the dynamics of how people occupy housing or the complexities that arise when, for example, someone might rent accommodation while owning a house elsewhere. Most censuses and surveys simply ask whether the household living in a sampled house (or apartment, etc) currently rents or owns that house. I find access to housing to be a better analytical category than tenure arguing that renting and owner occupier housing are not exclusive categories, and can co-exist, and that additional categories should be identified.